2012
DOI: 10.1136/acupmed-2011-010126
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture Enhances Motor Recovery Performance with Brain-Derived Neurotrophic Factor Expression in Rats with Cerebral Infarction

Abstract: Objective Electroacupuncture (EA) is a traditional medicine in patients with post-stroke rehabilitation. Brain-derived neurotrophic factor (BDNF) is a potent growth factor involved in recovery following cerebral injury. The aim of the present study was to investigate whether EA increases BDNF levels and facilitates functional recovery. Methods Occlusion of the middle cerebral artery was performed in rats (N=12) followed by reperfusion. EA was applied at the GV20 (Baihui) acupoint. Motor and sensory functions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 44 publications
0
27
0
4
Order By: Relevance
“…12 15 The potential effect on heat shock protein 40 enhances brain-derived neurotrophic factor expression. 41 Therefore, EA may be a useful treatment option for patients who experience TBI because of its multiple effects, and its use in the acute stage might have clinical benefits worth studying.…”
Section: Discussionmentioning
confidence: 99%
“…12 15 The potential effect on heat shock protein 40 enhances brain-derived neurotrophic factor expression. 41 Therefore, EA may be a useful treatment option for patients who experience TBI because of its multiple effects, and its use in the acute stage might have clinical benefits worth studying.…”
Section: Discussionmentioning
confidence: 99%
“…However, delivery of BDNF remains a substantial challenge for clinical trials because it is a moderately sized and charged protein and only minimal amount of BDNF administrated peripherally crosses the BBB to reach neurons in the brain. Acupuncture has been reported to increase neurotrophic factors [124] and the levels of nerve growth factors in the brain by altering the permeability of the BBB [125]. In rats, electric acupuncture enhanced motor recovery after cerebral infarction that was associated with increased expression of BDNF in the brain.…”
Section: Can “Chemobrain” Be Properly Studied Prevented or Correcmentioning
confidence: 99%
“…It has been reported that EA treatment exerted its neuroprotective effects through a series of mechanisms, including reducing the apoptosis of neural cells and inhibiting the inflammatory responses (22). In addition, EA treatment has been found to enhance neurogenesis via the upregulation of neurotropic factors, including BDNF (30). However, the impact of EA treatment on the proliferation and differentiation of NSCs remains to be elucidated.…”
Section: Discussionmentioning
confidence: 95%